Prevalence and risk factors for fatigue among breast cancer survivors on aromatase inhibitors. (September 2018) - Mao, Huijuan; Bao, Ting; Shen, Xueyong; Li, Qing; Seluzicki, Christina; Im, Eun-Ok; Mao, Jun J.
Abstract: Purpose: Fatigue is the most common and distressing symptom experienced by cancer survivors. This study sought to determine the prevalence and risk factors for fatigue among breast cancer (BC) survivors receiving aromatase inhibitors (AIs). Material and methods: We conducted a cross-sectional survey study among postmenopausal women with stage 0 to III BC receiving adjuvant AI therapy at the outpatient breast oncology clinic of a large university hospital. Participants with a score ≥4 on the 'worst fatigue' item of the Brief Fatigue Inventory were classified as having moderate or severe fatigue. Multivariate logistic regression analyses were performed to evaluate risk factors. Results: Among 1103 participants, 616 (55.8%) had moderate or severe fatigue. In the multivariate logistic regression model, women younger than 55 years were significantly more likely to report moderate to severe fatigue than women older than 65 years (adjusted odds ratio [AOR] = 1.58, 95% confidence interval [CI] = 1.07–2.35; p = 0.023). Compared to women with high school or less education, women with college or more education were significantly more likely to report moderate to severe fatigue (AOR = 1.40, 95% CI = 1.02–1.91; p = 0.037). Increasing body mass index (BMI) was significantly associated with increased risk of experiencing moderate to severe fatigue (overweight: AOR = 1.37, 95% CI = 1.01–1.84, p = 0.042; obesity: AOR = 2.08, 95% CI = 1.53–2.81, p < 0.001). Fatigue was significantly correlated with pain severity (r = 0.48, p < 0.001) and insomnia (r = 0.62, p < 0.001). Conclusion: Moderate to severe fatigue complaints exceed 50% among AI users. Fatigue is highly related to younger age, higher education level, higher BMI, pain severity and insomnia. Highlights: Moderate to severe fatigue complaints exceed 50% among aromatase inhibitor users. Obesity, younger age and higher education level were significantly associated with fatigue. The majority who experienced either pain or insomnia reported moderate to severe fatigue.